La Guardino, P. (2018). La marcha fúnebre. Una historia de la guerra entre México y Estados Unidos. Grano de Sal. 534 pp. - Segura Muñoz, Iván (Letras Históricas E-ISSN: 2448-8372, 2020)
Reseña de libro.